2020
DOI: 10.2147/cmar.s246385
|View full text |Cite
|
Sign up to set email alerts
|

<p>Mean Platelet Volume Has Prognostic Value in Chronic Lymphocytic Leukemia</p>

Abstract: Purpose: Mean platelet volume (MPV) is a readily accessible and commonly tested hematological indicator. Recent studies revealed a significant impact of MPV on the course and prognosis of many diseases, including some types of cancer, as well as on the incidence of atrial fibrillation and bleeding. The study aimed to perform a retrospective analysis of MPV in terms of time to first treatment (TTFT) and to determine its prognostic value in the group of patients with chronic lymphocytic leukemia (CLL). Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Interestingly we found that low platelet counts were associated with poor outcome in the whole and hospitalized patient cohort. Platelets have been discussed to modify course of the disease in various cancers, including CLL [20,21]. It was shown that thrombocytopenia was associated with poor outcome of COVID-19 patients in intensive care units [22].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly we found that low platelet counts were associated with poor outcome in the whole and hospitalized patient cohort. Platelets have been discussed to modify course of the disease in various cancers, including CLL [20,21]. It was shown that thrombocytopenia was associated with poor outcome of COVID-19 patients in intensive care units [22].…”
Section: Discussionmentioning
confidence: 99%
“…No studies have reported a link between PDW and ibrutinib treatment or bleeding events. Furthermore, MPV is not associated with ibrutinib therapy complications, including atrial fibrillation and bleeding [47]. All ibrutinib treated patients but one had a normal platelet count, implicating that the effect observed due to ibrutinib treatment is not due to low platelet count but due to a potential role of ibrutinib on platelet function.…”
Section: Discussionmentioning
confidence: 86%
“…In chronic inflammation, large platelets were found to be released from bone marrow induced by pro-inflammatory cytokines, then later, these platelets were depleted on ongoing inflammation and a significant drop on MPV levels could be seen in patients with chronic inflammation [10] [11] . Also, chronic proinflammatory cytokine release could lead to release of small therefore low-MPV platelets so, MPV and PCT levels could be found to be decreased [28] . These mechanisms should be responsible for low PCT associated poor outcome in CLL.…”
Section: Discussionmentioning
confidence: 99%
“…In diffuse large B cell lymphoma, two studies have shown that low MPV was associated with worse prognosis [29] [30] . Masternak et al, found that low MPV was associated with adverse outcome in CLL; patients who need treatment had lower MPV levels compared to patients who did not need any [28] . Also, low MPV was associated with shorter time for treatment and a tendency to lower MPV levels was seen as Rai stage advances besides from stage IV in this study.…”
Section: Discussionmentioning
confidence: 99%